A Case of Primary Squamous Cell Carcinoma of the Liver Arising in a Solitary Cyst. Issue 3 (1992) - Nieweg, O.; Slooff, M. J. H.; Grond, J.
Abstract : A case of primary squamous cell carcinoma in a pre-existing hepatic cyst is presented. A review of the literature suggests that this rare type of liver tumor tends to arise from solitary, nonparasitic cysts, lined with squamous epithelium. Effective therapy is not available, the prognosis is grave.